PEMANFAATAN ARANG AKTIF DARI KULIT DURIAN (Durio zibethinus L.) SEBAGAI ADSORBEN ION LOGAM KADMIUM (II) - Marlinawati -; Bohari Yusuf; Alimuddin - (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2015)
The research of adsorption cadmium (II) metal ions in the solution by activated carbon from durian peel has been done. Adsorption process is done by using a variation of pH (1, 2, 3, 4, 5 and 6), variation of contact time (15, 30, 45, 60, 75 dan 90 menit), variation of the concentration (20, 30, 40, 50 dan 60 mg/L). Analysis of metal ion concentration of cadmium (II) used by Atomic Absorption Spectrophotometer (AAS). The results of this research shows that the optimum condition was achieved at the pH value of 4 and the contact time of 60 minutes. Metal ion adsorption of cadmium (II) by activated carbon from durian’s peel at pH value of 4 and the contact time of 60 minutes can achieve 64,540%. Metal ion adsorption capacity of cadmium (II) adsorbed by activated carbon from durian’s peel can achieve 0,4951 mg/g.Keywords : Adsorption, Activated Carbon, Durian Peel, Metal Ions Cadmium (II)